The Oxford dictionary of dance - Salih, Al-Tayyib.; Mackrell, Judith; Oxford eBooks ([Oxford] : Oxford University Press, 2010)
This comprehensive and up-to-date dictionary provides all the information necessary for dance fans to navigate the diverse dance scene of the 21st century. It includes entries ranging from classical ballet to the cutting edge of modern dance.
"Oxford Reference Online Premium."
Title from title page (viewed on Aug. 27, 2010).
Also issued in print format.
Includes bibliographical references.
Keywords: Dance -- Dictionaries; Electronic books